THE EFFECT OF COFFEE AND RUBBER IMPORTS EXPORTS ON FOREIGN EXCHANGE RESERVES IN INDONESIA - Hijri Juliansyah; Muhammad Ikram; Ratna; Umaruddin Usman; Ahmad Zubair (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine the effect of exports and imports of coffee and rubber on short run and long run of foreign exchange reserves in Indonesia. The study uses a time series data in the year 1990-2021 obtained from the world bank and Food and Agriculture Organization (FAO). This study employs the Autoregressive Distributed Lag (ARDL) model. The results showed that in the short run coffee exports have a positive and significant effect on Indonesia's foreign exchange reserves, whereas in the long run coffee exports have no effect on Indonesia's foreign exchange reserves. The coffee import has a negative and significant effect on Indonesia's foreign exchange reserves in the short run but in the long run it has a positive and significant effect on Indonesia’s foreign exchange reserves. The rubber exports in the short run, it has a positive and significant effect on Indonesia's foreign exchange reserves, while in the long run rubber exports have no effect. While rubber imports in the long run and short run have a positive and significant effect on foreign exchange reserves in Indonesia.